Surgical management of varicose veins: a comparative analysis between radiofrequency ablation and open surgery with venous stripping - Naithani, Vinay; Chanda, Dinesh Kumar; Bhatiya, Budhi Prakash; Sharma, Ashok Kumar (International Surgery Journal, 2020)
Background: Varicose veins are a common condition affecting the lower limbs. Apart from having cosmetic problem, if not treated in time it can have some serious complications and are difficult to treat. Multiple modes of surgical management exist for the disease. Methods: This is a prospective clinical study, done over a period of 5-years, between February 2015 to February 2020. Patients were divided into 2 groups: group I (n=103) included those who underwent open surgical to treatment with venous stripping. Group II (n=104) included those who subjected to Radiofrequency ablation (RFA). Groups were selected with comparable physical parameters. Various parameters like bleeding, hematoma, blood requirement, postoperative inflammation, pain, numbness, mobilization, date of discharge and resuming duties were compared. All patients were followed up for 1y ear. Results: Majority of our patients belongs to age group 20-40 years with mean age of 35year in both groups. Male has dominance over female with male to female ratio 4:1. We noticed significant complication in group I than group II, such as bleeding (20:1), hematoma (5:0), inflammation (60:1) and blood requirement (1:0). In group II, we noticed early mobilization of patient (1day v/s 3 days), discharge from hospital (1day v/s 5 days) and resuming duties (5 days v/s 2 weeks). Conclusion: RFA keeps an edge over open surgical treatment with venous stripping.